Nursing student’s perception about the profession - Francisco Emmanuel Miranda de Sousa; Eliany Nazaré Oliveira; Joyce Mazza Nunes; Roberlândia Evangelista Lopes; Fabiane do Amaral Gubert (Rev Rene)
The aim of this study is to identify the perceptions of new students in the graduate nursing course about the profession. This qualitative study was conducted from March to May 2008, along with 38 first year students from a public university of Ceará. Data collection occurred through five meetings, in daily field notes and projective drawing technique based on the questioning: What is nursing for you? The results show enhancement of the hospital as a field, followed by care in primary health care. The students recognize nursing as a possibility of financial growth, and emphasize the importance of support, assistance and solidarity with the patients. The study allows students to identify the perceptions of nursing and make them reflect about the need for new positions and recognition of the role of the nurse, regardless of the performance setting.